A characterization of the existence of generalized stable sets - Andrikopoulos, Athanasios (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The generalized stable sets solution introduced by van Deemen (1991) as a generalization of the von Neumann and Morgenstern stable sets solution for abstract systems. If such a solution concept exists, then it is equivalent to the admissible set appeared in game theory literature by Kalai and Schmeidler (1977). The purpose of this note is to provide a characterization for the existence of the generalized stable sets solution.